KELAYAKAN ISI DAN BAHASA TEKS NEGOSIASI PADA BUKU TEKS KELAS X DI SMK SEMESTA BUMIAYU - Nasikha, Latifatun (Hasta Wiyata, 2024)
This research aims to describe, analyze and explain the appropriateness of the content and appropriateness of the language in class X Indonesian language textbooks at SMK Semesta Bumiayu. The research method used in this research is a qualitative descriptive method with an evaluation approach model. The research data is in the form of Indonesian language textbooks for class X SMK Semesta Bumiayu. Furthermore, data collection techniques in this research include observation, interviews and document analysis. The data analysis technique was carried out in steps, namely interviews with teachers and students regarding the appropriateness of the content and language in the class X Indonesian language textbook, reading the data source in the form of the class X Indonesian language textbook, describing the material contained in the class book quality assessment using content and language suitability tests based on BNSP, and drawing conclusions. The data validity technique is carried out by triangulating data sources and theory. The research results show that the appropriateness of the content includes, (1) suitability of the material description with the core competencies and basic competencies contained in the curriculum of the subject concerned, (2) accuracy of the material, and (3) teaching supporting material. Meanwhile, appropriateness of language includes (1) suitability of language use to the student’s level of development, (2) use of communicative language, (3) use of language that meets the requirements for coherence and integration of thought flow.